2019
DOI: 10.1016/j.acra.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Multibreath Hyperpolarized 3He Imaging Scheme to Measure Alveolar Oxygen Tension and Apparent Diffusion Coefficient

Abstract: Rationale and Objective: In this study, we compared a newly developed multi-breath simultaneous alveolar oxygen tension and apparent diffusion coefficient (P A O 2-ADC) imaging sequence to a single-breath acquisition, with the aim of mitigating the compromising effects of inter-voxel flow and slow-filling regions on single-breath measurements, especially in COPD subjects. Materials and Methods: Both single-breath and multi-breath simultaneous P A O 2-ADC imaging schemes were performed on a total of ten human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…These appear in three forms. As has been discussed previously [ 18 , 19 ], mixing from different regions can result in negative p A O 2 values. In addition, mixing can also create the opposite effect, namely that p A O 2 results with values greater than the oxygen partial pressure of air can be recorded.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These appear in three forms. As has been discussed previously [ 18 , 19 ], mixing from different regions can result in negative p A O 2 values. In addition, mixing can also create the opposite effect, namely that p A O 2 results with values greater than the oxygen partial pressure of air can be recorded.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, 3 He gas flowing to neighboring voxels during the p A O 2 acquisition results in partial pressure measurements that are negative [ 18 ]. Subsequent studies using HP 3 He and more sophisticated multi-breath imaging techniques [ 19 ] partially alleviate this difficulty, but with some loss in the signal-to-noise ratio (SNR). In parallel to studies of p A O 2 from HP 3 He MRI, ADC measurements on COPD participants have reached a quite advanced stage of development and suffer less from systematic uncertainties and provide a metric complementary to CT data for characterizing emphysema subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many of the included studies also observed significant correlations between FEV1 and hyperpolarized 3 He MRI measured ventilation defect volume (r = À0.53; p = 0.04 21 ; r = À0.58; p = 0.007 29 ) or ventilation defect percentage (r = À0.42; p = 0.2 15 ; r = À0.55; p = 0.03 21 ; r = À0.84; p < 0.001 25 ). Also, significant correlations were observed between DLCO and hyperpolarized 3 He MRI measured ventilation defect percentage (r = À0.83; p = 0.0001 14 and r = À0.61; p = 0.04 25 ).…”
Section: Discussionmentioning
confidence: 86%
“…By reducing breath-hold lengths and more closely representing physiological breathing, multi-breath hyperpolarized (HP) gas imaging has been shown to reduce artifact-induced heterogeneity and reveal "slow-filling" regions, therefore, enabling a more comprehensive evaluation of lung ventilation. [26][27][28] Here, we present an expanded multi-breath approach that incorporates compartment-selective XTC methodology 29,30 to simultaneously capture gas exchange with the tissue membrane and red blood cells (RBCs) in addition to regional ventilation. A model of per-breath gas replacement is then derived to describe the observed HXe signal profile and extract the ventilation and gas exchange parameters.…”
Section: Introductionmentioning
confidence: 99%